(untitled) (Perner’s Contacts, 2011)
The article deals with derived, algorithm design and description of the trigonometric polynomial. There are described and explained the basic computational procedures regarding this issue, first is always a theoretical analysis, followed by solved examples and extracts functions in Matlab with explanatory commentary.